Decision support system for determining capital investment value in biodiesel production using the net present value method - Irwansyah, Defi; Abdullah, Dahlan; Yunizar, Zara; Ardian, Zalfie; Arrahman, Fadly (Edelweiss Applied Science and Technology, 2024)
Biodiesel is a renewable alternative that is a biofuel for diesel engine/motor applications. It is a fatty acid methyl ester (FAME) that is produced from vegetable oil or animal fat and can be renewed. The esterification/ transesterification process results in low CO2/CO2 emissions. Indonesia’s energy consumption has increased by 7% annually in recent years, while the global energy consumption has only increased by 2% annually. This condition accelerates the rate of exploitation of fossil resources, including oil, natural gas, and coal, in comparison to the discovery of new reserves (replace reserves ratio). Economic calculations are conducted during the pre-design phase of a biodiesel chemical plant to ascertain the viability of investing in a biodiesel plant. The feasibility of capital investment in a factory production activity is estimated through the use of economic analysis, which involves the evaluation of capital requirements, predicted profits, payback period, taxes imposed, and break-even point. Furthermore, economic analysis is also used to ascertain the profitability of a factory that has been designed. The net present value (NPV) method is employed to develop a decision support system that simplifies the investment calculation process. In the present era of globalization, a company or investor must act promptly to make decisions and take action. The Net Present Value (NPV) method is used to assist in decision-making. The NPV method is a decision-making process that evaluates the feasibility of whether an investment is worthwhile. The value of an asset is determined by the initial purchase price and the time value of money, which are combined to calculate Net Present Value. The investment value of the SPK that has been designed is determined using the NVP procedure.